Impact of previous cesarean delivery on reproductive outcomes of assisted reproductive technology: a Bayesian network meta-analysis - Kun Ma; Shuo Jin; Chenhan Zhao; Rongyun Wang; Liuqing Yang; Jing Ma; Cong Gao; Lihua Sun; Qin Zhang; Ling Wang (Annals of Medicine)
Objective To systematically review the impact of vaginal delivery (VD), cesarean scar (CS), cesarean scar disorder (CSD) and intra-cavitary fluid (ICF) on the reproductive outcomes of women involving assisted reproductive technology (ART) based on Bayesian network meta-analysis.Methods Six databases were searched from the inception to October 16, 2024. Primary outcomes were clinical pregnancy rate and live birth rate. Secondary outcomes included positive human chorionic gonadotropin (hCG) test rate, miscarriage rate, ectopic pregnancy rate, and severe adverse pregnancy outcomes. Extracted study data were analyzed by pairwise and network meta-analysis using R software and Stata.Results This study revealed that CS, CSD and ICF significantly reduced clinical pregnancy rate (CS vs VD: RR = 0.88, 95% CI 0.78-0.99, p < 0.05; CSD vs VD: RR = 0.72, 95% CI 0.59-0.86, p < 0.05; ICF vs VD: RR = 0.63, 95% CI 0.46-0.82, p < 0.05), and live birth rate (CS vs VD: RR = 0.86, 95% CI 0.76-0.97, p < 0.05; CSD vs VD: RR = 0.65, 95% CI 0.52-0.79, p < 0.05; ICF vs VD: RR = 0.61, 95% CI 0.43-0.82, p < 0.05) compared to VD. Furthermore, CSD had a lower live birth rate than CS (RR = 0.75, 95% CI 0.59-0.95, p < 0.05); ICF decreased both clinical pregnancy rate (RR = 0.72, 95% CI 0.51-0.95, p < 0.05) and live birth rate (RR = 0.71, 95% CI 0.49-0.97, p < 0.05) compared with CS.Conclusions ICF, CSD, and CS all significantly reduce clinical pregnancy rate and live birth rate in women with ART. CSD and ICF had much lower live birth rate than CS. Notably, ICF was a prominent risk factor for these adverse reproductive outcomes.Trial registration Registered with PROSPERO on October 19, 2024, CRD42024603479.